2005
DOI: 10.1007/s10720-005-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

A general method for preparing tellurides: Synthesis of PbTe, Ni2Te3, and Cu7Te5 from solutions under microwave radiation

Abstract: Nanocrystals of binary metal tellurides, such as PbTe, Ni 2 Te 3 , and Cu 7 Te 5 , are synthesized by the polyol method under microwave radiation and studied using X-ray powder diffraction, transmission electron microscopy, high-resolution transmission electron microscopy, and photoacoustic spectroscopy. Binary tellurides are formed only in the case when ethylene glycol is used as a reducing agent and only when the reaction is carried out under microwave radiation. No product is formed when the reactions are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…As compared to the synthesis with the conventional heating methods, the microwave-assisted synthesis of metal chalcogenide nanostructures has an obvious advantage of rapidness, with much reduced preparation time often by orders of magnitude. Many kinds of nanostructured metal chalcogenides prepared by the microwave-assisted polyol method have been reported, including SnS, , SnS 2 , , PbS, , Sb 2 S 3 , , Bi 2 S 3 , , CdS, ZnS, ,, CuS, FeS 2 , CoS, Cu 3 BiS 3 , Cu 2 ZnSnS 4 , CdSe, , β-FeSe, Sb 2 Se 3 , , Bi 2 Se 3 , MoSe 2 , Cd 1– x Zn x Se, , CuInSe 2 , Sb 2 Te 3 , Bi 2 Te 3 , PbTe, Ni 2 Te 3 , Cu 7 Te 5 , Cu (2– x ) Te, and CuInTe 2 . EG has been commonly adopted as the solvent. ,,,, , , In addition, other polyols have also been used as the solvents, such as propylene glycol, , 1,2-propanediol, triethylene glycol, , 1,5-pentanediol, glycerol, ,…”
Section: Microwave-assisted Preparation Of Nanostructures In Polyolsmentioning
confidence: 99%
See 2 more Smart Citations
“…As compared to the synthesis with the conventional heating methods, the microwave-assisted synthesis of metal chalcogenide nanostructures has an obvious advantage of rapidness, with much reduced preparation time often by orders of magnitude. Many kinds of nanostructured metal chalcogenides prepared by the microwave-assisted polyol method have been reported, including SnS, , SnS 2 , , PbS, , Sb 2 S 3 , , Bi 2 S 3 , , CdS, ZnS, ,, CuS, FeS 2 , CoS, Cu 3 BiS 3 , Cu 2 ZnSnS 4 , CdSe, , β-FeSe, Sb 2 Se 3 , , Bi 2 Se 3 , MoSe 2 , Cd 1– x Zn x Se, , CuInSe 2 , Sb 2 Te 3 , Bi 2 Te 3 , PbTe, Ni 2 Te 3 , Cu 7 Te 5 , Cu (2– x ) Te, and CuInTe 2 . EG has been commonly adopted as the solvent. ,,,, , , In addition, other polyols have also been used as the solvents, such as propylene glycol, , 1,2-propanediol, triethylene glycol, , 1,5-pentanediol, glycerol, ,…”
Section: Microwave-assisted Preparation Of Nanostructures In Polyolsmentioning
confidence: 99%
“…609 The nanostructured metal tellurides have also been prepared by the microwave-assisted polyol method. Palchik et al 613 prepared nanostructured binary metal tellurides, such as PbTe, Ni 2 Te 3 , and Cu 7 Te 5 , by the microwave-assisted polyol method. Binary tellurides were formed only in the case when EG was used as a reducing agent under microwave irradiation.…”
Section: Metal Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyer et al [12] reported an enhanced thermoelectric efficiency of molecular beam epitaxially (MBE) grown superlattices based on PbTe. Palchik et al [13] synthesized PbTe from solutions under microwave radiations. Earlier works also reported the synthesis of 3-D structures of PbTe such as dendrite-like structures via electrochemical deposition [14] and sponge-like structures from sonochemistry [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured binary metal telluride, PbTe was prepared via MW‐assisted polyol method using EG was used as a reducing agent. [ 216 ] No product was observed when the reaction was performed using a conventional heating method.…”
Section: Traditional Versus Green Sustainable Te Materials Synthesis ...mentioning
confidence: 99%